مشترکہ خاندانی کاروبارکے انتظامی، شرعی اور اخلاقی مسائل اور اسلامی تعلیمات: Administrative, Sharī̒ah and Ethical Issues of Joint Family Business and Islamic Teachings (Al-Qamar, 2021)
Family business is a major cause of many problems in the family system and family affairs. Complications that arise under the influence of family business eventually lead to the collapse of the family system. How the social and economic system of the world is intertwined with family businesses can be gauged from the statistics that 85% of Europe, 90% of the United States, 98% of the Gulf countries, 75% of Spain. While almost 90% of the economies of India and Pakistan are dependent on family business, the one-sided spectacle is that 90-95% of family businesses do not survive after the third generation. On the other hand, its failure rate is almost 100%. There is no doubt that the second meaning of the destruction of family business is the destruction of families. In the midst of this situation, we need to look at the issues that bring the family business and then the entire family system to the brink of collapse. Management in Family Businesses: Lack of Succession Planning of Succession, Mutual Mutability, Confusion of Domestic and Business Matters and Lack of Proper Determination of Ownership and Rights. Indefinite status of participants in the partnership, negligence in the legal distribution of inheritance, non-existence of matters in writing and a series of ambiguities in matters. On the other hand, from the moral point of view: lack of compassion and the practice of deprivation of mercy, lack of justice, non-payment of zakat and financial rights and financial corruption and oppression and abuse. By solving these problems not only families can be saved and family affairs can be improved, but also joint family business can be successful and prosperous. These issues and solutions are mentioned in the article under review.
Keywords: Family; business; partnership; Islam